Pengaruh Citra Merek Tas Michael Kors Indonesia Terhadap Minat Beli (Survei kepada Pengikut Instagram @shopatbanananina) - Nabilla Sarah Shafia (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The desire of consumers to pursue social status and the urge to be recognized for their fashion awareness is one of the causes of the increasing demand for world-renowned luxury branded products. Michael Kors as one of the manufacturers of affordable luxury branded bags, spreads its wings by cooperate with bag manufacturers in Indonesia to make their products. Michael Kors bags from Indonesia then entered the Indonesian market through luxury bag boutiques. One of them is Banananina that sells it online through Social Media Instagram under name @shopatbanananina, or directly in their shop. This study aims to determine the effect of Michael Kors Indonesia's Bag Brand Image on Buying Interest (Survey of Instagram Followers @shopatbanananina). The method used in this study is an associative explanatory survey which aims to find data with several variables that can be measured in a questionnaire. The results of this study indicate that 55.8% of respondents stated that the Michael Kors Indonesia Brand has a positive brand image that greatly influences consumer buying interest in their products, while the value of consumer buying interest in Michael Kors Indonesia products is 53.4% ​​stating that a good product image , famous, quality, and classy is directly proportional to the price of the product listed does not become an obstacle for consumers to have an interest in buying and decide to make a purchase of the product.